THE ROLE OF MIGRANT ASSOCIATIONS IN LANGUAGE EDUCATION OF UKRAINIAN CHILDREN WITH MIGRANT BACKGROUND IN PORTUGAL - Natalia Gut (Pavlo Tychyna Uman State Pedagogical University, 2017)
The article analyses the role the migrant associations play in language education of children with migrant background. The presented research assumes language education of migrants as the process of learning language of host country and other foreign languages as well as mastering the language of the country of origin. It is stated that in Portugal mother tongue tuition is usually offered outside the state school framework and the Ukrainian language education is organised and funded by voluntary and private initiatives, one of which is migrant communities themselves. Different migrant associations and their centres in Portugal have been described. Protecting the rights and interests of immigrants and their descendants, strengthening positive attitude to Ukrainians and Ukrainian state, supporting and developing Ukrainian national identity, spirit, language, culture and heritage of Ukrainians who reside or stay in Portugal were proved to be among the main tasks of their creation. The associations of Ukrainians were said to contribute to non-formal education of Ukrainian children as Saturday schools founded by these organizations provide organized educational activity outside the established formal system. The article is based on the mixed research conducted at Ukrainian Saturday school to find out the possible achievements in the process of Ukrainian language acquisition among Ukrainian students in Portugal. The presented results show that the children have profit from functioning such public associations as they have the opportunity to overcome the feelings of rejection to tuition given outside the standard curriculum and school hours, to be motivated to study native language and develop their knowledge by means of mother tongue, to preserve their identity and language in the society of the host country.